2012
DOI: 10.1002/mrc.2854
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intramolecular and intermolecular coordination on 31P nuclear shielding: phosphorylated azoles

Abstract: The effects of intramolecular and intermolecular coordination on (31)P nuclear shielding have been investigated in the series of tetracoordinated, pentacoordinated and hexacoordinated N-vinylpyrazoles and intermolecular complexes of N-vinylimidazole and 1-allyl-3,5-dimethylpyrazole with phosphorous pentachloride both experimentally and theoretically. It was shown that either intramolecular or intermolecular coordination involving phosphorous results in a dramatic (31)P nuclear shielding amounting to approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…53,55 Intra-or intermolecular coordination involving phosphorus results in a dramatic 31 P nuclear shielding amounting to approximately 150 ppm upon changing the phosphorus coordination number by one. Namely, if molecules in solution are prone to association or selfassociation, the isolated molecular model will not be correct.…”
Section: ''Difficult'' Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…53,55 Intra-or intermolecular coordination involving phosphorus results in a dramatic 31 P nuclear shielding amounting to approximately 150 ppm upon changing the phosphorus coordination number by one. Namely, if molecules in solution are prone to association or selfassociation, the isolated molecular model will not be correct.…”
Section: ''Difficult'' Casesmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] In several systematic studies it was shown 48-55 that a satisfactory agreement between calculations and experiments is observed when quite a ''heavy'' basis set or high level of theory ‡ was used although deviations and exceptions were also found. In fact, there are relatively few reports on 31 P NMR CS calculations using quantum chemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Specific solvation of 93( E ) , 93( Z ) , and 94( Z ) with nitromethane reported by Chernyshev, et al had been investigated by adding several molecules of CH 3 NO 2 into solvation cavity, the latter in turn being polarized within the IEF‐PCM scheme, thereby accounting for the electrostatic, dispersion–repulsion, and cavitation nonspecific solvation effects. It followed that 31 P NMR chemical shifts calculated for isolated molecules were in a reasonably good agreement with experiment for 93( E ) and 94( Z ) , whereas in the case of 93( Z ) , theoretical values exceeded experiment by about 150 ppm.…”
Section: Computation Of 31p Nmr Chemical Shifts: Accuracy Factors Andmentioning
confidence: 92%
“…A year later, Chernyshev, et al performed a systematic study of solvent effects on 31 P NMR chemical shifts in the phosphorus derivatives of N ‐vinylimidazole ( 92 ) in its intermolecular complexes with phosphorus pentachloride, the products of its phosphorylation, namely, tetra‐, penta‐, and hexacoordinated N ‐vinylpyrazoles 93( E ) , 93( Z ) , and 94( Z ) shown in Scheme . It was demonstrated that either intramolecular or intermolecular coordination involving phosphorus results in a dramatic 31 P NMR shielding amounting by as much as 150 ppm on changing phosphorus coordination number by one, which indicated the major importance of solvent effects on 31 P NMR chemical shifts of intramolecular and intermolecular complexes with N → P coordinate bond.…”
Section: Computation Of 31p Nmr Chemical Shifts: Accuracy Factors Andmentioning
confidence: 99%
See 1 more Smart Citation